Optimizing structural performance of Savonius turbine blades through comparative analysis of mechanical properties - Mat Yazik M.H.; Ishak M.H.H.; Chang W.S.; Ismail F.; Zawawi M.H.; Ahmed A.N.; Mohd Sidek L.; Basri H. (American Institute of Physics, 2025)
Savonius turbine is an alternative wind turbine design that has the ability for self-starting from static condition at different blade angle. There are concerns in the structural behavior of the materials used for the Savonius turbine blades under aerodynamic loads. This study aims to optimize the structural and material properties of Savonius wind turbine blades by conducting a comparative analysis of maximum stress and deformation across different materials. This research involves creating detailed numerical models of the turbine blades using Finite Element Analysis to simulate the mechanical behavior under operational loads. Wood, Aluminum, and Steel are investigated to examine its effect of structural performance in the static conditions. In addition to solid isotropic materials, anisotropic materials such as Carbon Fiber and Glass Fiber composites are investigated. Ansys Composite Prepost is used to access the mechanical properties of composites. Initial analysis shows that the deformation is highly dependent on the Young's modulus of each material. Due to the dependency of composite on the fiber properties, a multi-objective optimization is defined to optimize these parameters on a five-layer composite structure to minimize stress, deformation, and weight. It was found that Carbon-Fiber composites exhibit better performance compared to other materials with improvement up to 22% in maximum deformation. These findings highlight the potential for substantial improvements in blade efficiency and durability through careful material selection and optimization. These findings can be utilized for a preliminary design of Savonius wind turbines and other renewable energy sector, where optimizing wind turbine performance is crucial for sustainable energy production to find optimum composite configuration without compromising its aerodynamic performance. ? 2024 Author(s).